BIBLIOMETRIC ANALYSIS OF ANTI-CORRUPTION CAMPAIGN RESEARCH IN INDONESIA WITH THE GOOGLE SCHOLAR DATABASE - Muh Nurkhamid (Jurnal Scientia, 2023)
With a qualitative method in the form of bibliometric analysis from the Google Scholar Database, this research shows that the number of research and / or publications related to the Anticorruption Campaign in Indonesia from 2004 to 2022 is volatile, even in some years the number is 0 (zero). In addition, the results showed that the activities of the Anticorruption Campaign in Indonesia have used several media and are aimed at several categories of audiences in the community. The five words that often come up and should be of concern to subsequent researchers are campaign, anti-corruption, corruption, social campaign, and film. The suggestion for further research is to expand the Anticorruption Campaign research to some audiences that are relatively at great risk of corruption, for example village communities managing village funds.